Correlation between radiation damage and magnetic properties in reactor vessel steels - Kempf, Rodolfo A.; Sacanell, Joaquin Gonzalo; Milano, Julian; Guerra Mendez, Nicolas; Winkler, Elin Lilian; Butera, Alejandro Ricardo; Troiani, Horacio Esteban; Saleta, Martin Eduardo; Fortis, Ana Maria (Elsevier Science, 2014)
Fil: Kempf, Rodolfo A.. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes. Gerencia de Investigación y Aplicaciones; Argentina